A Time-Delay Overlapping Modulation-Based Maritime High-Speed and High-Spectral-Efficiency Communication Technology - Xinyu Dou; Teng Ma; Dequn Liang (Journal of Marine Science and Engineering)
To simultaneously address dual demands on the spectral efficiency and the data transmission rate of maritime communications, in this paper, a novel maritime communication technology based on time-delay overlapping modulation (TDOM) is proposed. In TDOM, multiple carriers are delayed in turn and directly overlapped in the time domain to form the communication symbol. In this way, the strict orthogonality between carriers can be broken through, indicating that the frequency interval between carriers can be much narrower than ever. In other words, TDOM can achieve non-orthogonal communication and realize both higher spectral efficiency and a higher maritime communication rate. The system architecture is designed, and its performance is analyzed and compared with that of other typical maritime communication technologies such as the very-high-frequency data exchange system (VDES). It is shown that TDOM can reach up to 20 times the peak communication rate and the spectral efficiency of VDES. As a digital modulation technology implemented in the physical layer, the proposed TDOM can be extended to other communication systems such as satellite communications or 4G/5G based off-shore communications.